DERIVATION OF INTERNALLY-CONSISTENT THERMODYNAMIC DATA BY THE TECHNIQUE OF MATHEMATICAL PROGRAMMING: A REVIEW WITH APPLICATION THE SYSTEM MGO-SIO2-H2O - Berman R.G.; Engi M.; Greenwood H.J.; Brown T.H. (My University, 1986)
The problem of deriving an optimal set of thermodynamic properties of minerals from a diverse experimental data base is reviewed and a preferred methodology proposed. Mathematical pro-gramming(MAP) methods extend the linear programming (LIP) approach first presented by Gordon (1973), and make it possible to account for the type of information conveyed, and the uncertainties attending